2D Photovoltaic Devices: Progress and Prospects. Issue 3 (26th January 2018) - Wang, Lin; Huang, Li; Tan, Wee Chong; Feng, Xuewei; Chen, Li; Huang, Xin; Ang, Kah‐Wee
Abstract: The discovery of the new class of 2D materials has stimulated extensive research interest for fundamental studies and applied technologies. Owing to their unique electronic and optical properties, which differ from their bulk counterparts and conventional optoelectronic materials, 2D materials at the atomic scale are very attractive for future photovoltaic devices. Over the past years, their great potential for photovoltaic applications has been widely investigated by creating a variety of specific device structures. Here, the recent progress made toward the exploitation of 2D materials for high‐performance photovoltaic applications is reviewed. By addressing both lateral and vertical configurations, the prospects offered by 2D materials for future generations of photovoltaic devices are elucidated. In addition, the challenges facing this rapidly progressing research field are discussed, and routes to commercially viable 2D‐material‐based photovoltaic devices are proposed. Abstract : 2D materials represent a promising family for the future generations of photovoltaic devices requiring high efficiency, light weight, flexibility, and transparency. The progress and prospects of 2D photovoltaic devices are comprehensively reviewed and discussed. Key challenges associated with this technology are identified and future research directions in this rapidly developing field are proposed.